Phosphonate Modified Silica for Adsorption of Co(II), Ni(II), Cu(II), and Zn(II) - Dian Maruto Widjonarko; Jumina Jumina; Indriana Kartini; Nuryono Nuryono (Indonesian Journal of Chemistry, 2014)
A new phosphonate modified silica (PMS) has been investigated for adsorption of Co(II), Ni(II), Cu(II), and Zn(II) in aqueous solution. The adsorbent was modified of silica by immobilizing aminoethyl dihydrogen phosphate (AEPH2) on 1,4-dibromobutane grafted silica. The physicochemical of the adsorbent was investigated using Fourier Transform Infra-red (FTIR) spectroscopy, X-ray Fluorescence (XRF), and N2 gas adsorption/desorption. The adsorption study was carried out in a batch system by mixing solution of metal ions at various pHs, contact times, and initial metal ion concentrations. The unadsorbed metals were determined by Flame Atomic Absorption Spectrophotometry (FAAS). Result of characterization showed that PMS has been successfully prepared. The product contained 45.99% (w/w) silica and 1.33% (w/w) phosphorous with surface area, pore volume, and pore size of 115.3 m2g-1; 0.7578 mLg-1; and 131.44 Å, respectively. Adsorption of metal ions on PMS occurred quite fast, less than 30 min. Modification of phosphonate on silica increased the adsorption capability, up to 8 times higher than that of unmodified silica, depending on metal ion type and pH solution. The capacity order of the metals adsorption was Cu(II)>Co(II)>Ni(II)>Zn(II). Based on the adsorption characteristic, the adsorbent is promising to be applied as a material for solid phase extraction of transition metal ions.